Turing Instability in aPathogen Host Immune Model with Diffusion - WANGJingnan; YANGDezhong; LULanfen (Journal of Harbin University of Science and Technology)
In order to study the effects of diffusion function on the dynamics between pathogens and host immune cells，a reaction-diffusion model of pathogen-host immune with homogeneous Neumann boundary condition is constructed. Taking the diffusion ratio ρ of pathogens and immune cells as a parameter，the critical conditions of Turing instability are obtained by using partial differential equation theories to discuss the characteristic root distribution of the linearized system at the positive equilibrium solution. Matlab numerical simulations are performed to show the dynamic phenomenon of Turing instability in the pathogen-host immune model. Furthermore，diffusion mechanisms of the pathogen and immune cell in the dynamic phenomenon of Turing instability are discussed.